Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Microwave-assisted synthesis and humidity sensing of nanostructured alpha-Fe2O3 - Deshmukh, Rupali G.; Badadhe, Satish S.; Mulla, Imtiaz S. (Materials Research Bulletin, 2009)
Nanocrystalline alpha-Fe2O3 has been prepared on a large-scale by a facile microwave-assisted hydrothermal route from a solution of Fe(NO3)(3)center dot 9H(2)O and pentaerythritol. A systematic study of the morphology, crystallinity and oxidation state of Fe using different characterization techniques. Such as transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy was performed It reveals. that nanostructured alpha-Fe2O3 comprises bundles of nanorods with a rhombohedral crystalline Structure. The individual nanorod has 8-10 nm diameter and similar to 50 nm length. The as-prepared nanostructured alpha-Fe2O3 (sensor) gives selective response towards humidity. The sensor shows high sensitivity, fast linear response to change in the humidity with almost 100% reproducibility. The sensor works at room temperature and rejuvenates without heat treatment. The as-prepared nanostructured alpha-Fe2O3 appears to be a promising humidity sensing material with the potential for commercialization. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrical properties; Nanostructures; Oxides; X-ray diffraction

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures

Low temperature pH dependent synthesis of flower-like ZnO nanostructures with enhanced photocatalytic activity - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Materials Research Bulletin, 2011)
In the present study we have synthesized flower-like ZnO nanostructures comprising of nanobelts of 20 nm width by template and surfactant free low-temperature (4 degrees C) aqueous solution route. The ZnO nanostructures exhibit flower-like morphology, having crystalline hexagonal wurtzite structure with (001) orientation. The flowers with size between 600 and 700 nm consist of ZnO units having crystallite size of similar to 40 nm. Chemical and structural characterization reveals a significant role of precursor: ligand molar ratio, pH, and temperature in the formation of single-step flower-like ZnO at low temperature. Plausible growth mechanism for the formation of flower-like structure has been discussed in detail. Photoluminescence studies confirm formation of ZnO with the defects in crystal structure. The flower-like ZnO nanostructures exhibit enhanced photochemical degradation of methylene blue (MB) with the increased concentration of ligand, indicating attribution of structural features in the photocatalytic properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Defects; Nanostructures; Optical properties; Semiconductor